The Relationship Between Resilience and Psychological Well-Being of Mothers and Children with Autism During the Golden Age - Kadek Wira Ayu Pratiwi; Luh Putu Ratih Andhini; Ni Made Sintya Noviana Utami (Psikologi Prima, 2026)
The complexities of parenting for mothers of children with autism, particularly during the golden age (ages 0–6 years), present unique challenges. In this context, mothers are required to adapt to various emotional pressures and the atypical developmental dynamics of their children. Based on these considerations, this study aims to analyze the relationship between resilience and psychological well-being in mothers raising children with autism. This research employed a quantitative approach using a correlational method. The sample consisted of 10 mothers selected through purposive sampling at the Rumah Autis X. Data were collected using two psychological scales: the resilience scale adapted from Putri Nasution (2024), which includes seven aspects emotional regulation, impulse control, causal analysis, self-efficacy, optimism, empathy, and reaching out with a reliability coefficient of 0.854; and the psychological well-being scale adapted from Kusumawati (2022), comprising six main dimensions self-acceptance, positive relations with others, autonomy, environmental mastery, purpose in life, and personal growth with a reliability coefficient of 0.935. The findings indicate a positive relationship between resilience and psychological well-being in mothers of children with autism aged 0–6 years. Higher levels of maternal psychological resilience are associated with better psychological well-being. Notably, the aspects of reaching out and self-efficacy showed relatively higher mean scores and were associated with mother adaptive responses in facing parenting challenges during the golden age. However, these findings should be interpreted cautiously due to the limited sample size, which may affect the generalizability and statistical stability of the findings.